Recent Insights Into Processing Approaches and Potential Health Benefits of Goat Milk and Its Products: A Review - Nayik, Gulzar Ahmad; Jagdale, Yash D.; Gaikwad, Sailee A.; Devkatte, Anupama N.; Dar, Aamir Hussain; Dezmirean, Daniel Severus; Bobis, Otilia; Ranjha, Muhammad Modassar A. N.; Ansari, Mohammad Javed; Hemeg, Hassan A.; Alotaibi, Saqer S. (Frontiers in Nutrition, 2021)
Goat milk is considered to be a potential source of various macro- and micro-nutrients. It contains a good proportion of protein, fat, carbohydrates, and other nutritional components which help in promoting nutritional and desirable health benefits. Goat milk is considered to be superior in terms of numerous health benefits, and lower risk of allergy, when compared to the milk of other species. Several processing techniques such as pasteurization, ultrafiltration, microfiltration, and ultrasound have been employed to enhance the quality and shelf life of goat milk and its products. The diverse range of goat milk-based products such as yogurt, cheese, fermented milk, goat milk powder, and others are available in the market and are prepared by the intervention of advanced processing technologies. Goats raised in pasture-based feeding systems are shown to have a better milk nutritional composition than its counterpart. Goat milk contains potential bioactive components, which aids in the maintenance of the proper metabolism and functioning of the human body. This review gives insight into the key nutritional ingredients and bioactive constituents present in goat milk and their potential role in the development of various functional foods using different processing technologies. Goat milk could be considered as a significant option for milk consumption in infants, as compared to other milk available.